Chinese innovation in cardiovascular drug discovery. (December 2015) - Wang, Xin; Ji, Yong; Yang, Baofeng
Abstract : Linked Articles: This article is part of a themed section on Chinese Innovation in Cardiovascular Drug Discovery. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2015.172.issue-23